EFFECT OF SPECIES AND HARVEST MATURITY ON THE FATTY ACIDS PROFILE OF TROPICAL FORAGES - N. A. Khan; M. W. Farooq; M. Ali; M. Suleman; N. Ahmad; S. M. Sulaiman; J. W. Cone; W. H. Hendriks (Journal of Animal and Plant Sciences, 2015)
The aim of this study was to quantify the fatty acid (FA) content and composition of forages commonly fed to dairy animals in the tropics. Twelve forage species, namely, Trifolium alexandrinum, Cichorium intybus, Hordeum vulgare L., Medicago sativa, Avena sativa, Pennisetum purpureum, Setaria anceps, Sorghum almum, Panicum maximum, Rumex nepalensis, Panicum coloratum and Panicum antidotale were evaluated. Each forage species was grown in four replicate plots under standard agronomic conditions, and sampled at early, normal and late stages of maturity. The result of the present study showed that the chemical composition, dry matter digestibility and FA contents varied (P < 0.001) among forage species and harvest maturity. Linolenic acid (C18:3n-3), palmitic acid (C16:0) and linoleic acid (C18:2n-6) were the predominant FAs with an average content of 8.65, 3.61 and 2.38 g/kg dry matter (DM), contributing on average to 53%, 22% and 14% of the total measured FAs, respectively. Among the individual FAs, C18:3n-3 had the largest variation ranging from 4.26 to 17.43 g/kg DM at first harvest. The content of C16:0, C18:2n-6 and C18:3n-3 decreased (P < 0.001) with maturity, with the largest decrease being observed in C18:3n-3. This study highlights that harvest management is an important tool to manipulate the FA contents and composition within a forage species.
Keywords: Fatty acids; Grasses; Harvest maturity; Polyunsaturated fatty acids; Tropical forages